2018
DOI: 10.1002/ijc.31898
|View full text |Cite
|
Sign up to set email alerts
|

BET proteins regulate homologous recombination‐mediated DNA repair: BRCAness and implications for cancer therapy

Abstract: Bromodomain and Extra-Terminal (BET) proteins are historically involved in regulating gene expression and BRD4 was recently found to be involved in DNA damage regulation. Aims of our study were to assess BRD4 regulation in homologous recombination-mediated DNA repair and to explore novel clinical strategies through the combinations of the pharmacological induction of epigenetic BRCAness in BRCA1 wild-type triple negative breast cancer (TNBC) cells by means of BET inhibitors and compounds already available in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…Targeting cell cycle is a new emerging strategy that was particularly effective in luminal-like breast cancer in reverting endocrine resistance [93], but interesting data suggest a possible role of CDK4-6 inhibitors also as chemo-companions, since CDK6 may interfere with Pt-induced cell death through FOXO3 [94]. The present study, therefore, supports the rationale of finding optimal DNA-repair -focused companions, capable to both synergize with chemotherapy and to revert potential resistance mechanisms that could defeat the DNA -damaging potential of Pt-salts [12]. Synthetic lethality involving the inhibition of the APE1 endonuclease activity is only recently emerging in literature [95,96].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Targeting cell cycle is a new emerging strategy that was particularly effective in luminal-like breast cancer in reverting endocrine resistance [93], but interesting data suggest a possible role of CDK4-6 inhibitors also as chemo-companions, since CDK6 may interfere with Pt-induced cell death through FOXO3 [94]. The present study, therefore, supports the rationale of finding optimal DNA-repair -focused companions, capable to both synergize with chemotherapy and to revert potential resistance mechanisms that could defeat the DNA -damaging potential of Pt-salts [12]. Synthetic lethality involving the inhibition of the APE1 endonuclease activity is only recently emerging in literature [95,96].…”
Section: Discussionsupporting
confidence: 65%
“…As the anthracyclinebased regimen seems to bridge the gap between the NPM1 low and high groups, these data suggest that there is a subgroup of TNBC patients that not only is potentially prone to respond, but that could be burdened by a worse outcome if different therapeutic strategies were put in place. These results are of particular clinical interest since DNA-damaging strategies are an emerging opportunity for the treatment of TNBC, but a solid predictive marker is currently needed [12,17,92]. The inability to translate this difference on OS could be due to the small sample size, post-relapse treatments or underlying differences in terms of tumor biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches are currently under investigation, including the search for molecular targets, potential candidates for selective treatments [20]. For this purpose, targeting histone activity in regulating gene expression by acting on epigenome "readers" is a promising approach for the treatment of various malignancies, including TNBC [9,21,22]. In particular, JQ1 is a first-in-class selective BET bromodomain inhibitor [23], which acts by competitively binding with high affinity to the acetyl-lysine hydrophobic pocket of BRD4 [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to directly target these repair proteins, combining a PI3K pathway inhibitor and a PARP inhibitor has shown synergistic anti-tumor effects in SCLC and warrants further consideration for clinical trials [97]. Targeting epigenetic factors such as BET family members cause defects in DSB repair and might provide beneficial effects in combination with PARP inhibitors [98]. Preclinical studies using BET inhibitor and PARP inhibitor combination have shown the superior anti-tumor efficacy compared to either agent alone in various cancer types [99][100][101].…”
Section: Co-targeting the Rsr Pathway And The Dsb Repair Systemmentioning
confidence: 99%